SOCIOECONOMIC ADVERSITY AND ALLOSTATIC LOAD: A TWIN ANALYSIS - Robinette, J.K. (Innov Aging, 2017)
Childhood socioeconomic status (SES) is related to health concurrently and into adulthood, and is associated with adulthood SES. Given these far-reaching relationships, some question whether adulthood SES associates with health beyond childhood SES. Biometric twin (ACE) models partition the predictor variables into additive genetic (A), shared environmental (C), and nonshared (unique) environmental (E) variance components. Researchers can control for latent genetic and shared environmental factors that may confound conclusions about the causal effects of adulthood SES on health. We used family data from the second wave of the national Midlife in the United States (MIDUS) Study (128 MZ pairs, 99 DZ pairs, 119 Sibling pairs) to examine this question. Health was assessed with a measure of multi-system physiological dysregulation posited to confer risk for the development of physical health problems. Adult SES was calculated with education, family-adjusted poverty to income ratio, current financial situation, enough money to meet needs, and difficulty paying bills. Results of ACE models suggested that male twins with lower adult SES had higher allostatic load, indicating greater physiological risk, than their co-twins with higher SES (b = 0.19), adjusting for genetic and shared environmental correlations between allostatic load and SES, and observed childhood SES, health status, and perceived support from family and friends. This relationship was not observed among female twins. These results add to a growing literature indicating that lower adult SES is associated with poorer multi-system physiological health, even after accounting for shared genetic and early environmental influences.